Case Report: Progressive Cholestasis: Severe Phenotype of MEGDEL Syndrome With SATB2-Associated Syndrome - Su, Yajie; Zhang, Hui; Wang, Huijun; Wu, Bingbing; Yang, Jiao; Zhou, Wenhao; Li, Long (Frontiers in Pediatrics, 2021)
MEGDEL syndrome and SATB2-associated syndrome (SAS) are both rare congenital disorders with poor prognoses caused by gene mutations. We present the case of a 2-day-old girl with an unexplained abnormal liver function, feeding problem, and dystonia. Using next-generation sequencing, we identified two novel mutations in SERAC1 and a mutation in SATB2. Now, she is 15 months old and has the characteristics of SAS, such as downslanting palpebral fissures and delayed primary dentition. Besides the typical phenotypes of MEGDEL syndrome, such as hypertonia, failure to thrive, deafness, and motor regression, she has progressive cholestasis and is prone to high serum lactate after rehabilitation training and hypoglycemia with low ketone under starving conditions. These phenotypes substantially differ from the transient liver function abnormalities and hypoglycemia reported in the literature.